Role of Financial Rewards in Enhancing Academic Staff Performance in Public Universities in Uganda - Rwothumio, Joseph; Mbirithi, Daniel Mange; Itolondo, Wilfrida (East African Journal of Interdisciplinary Studies, 2020)
This article examined the financial reward practice implemented by universities to improve on the performance of lecturers in Uganda’s public universities. The main objectives of the research were to investigate the relationship between financial reward and teaching and research outputs of academic staff in selected public universities. A mixed method design using convergent parallel approach was employed to collect and analyse data obtained from the study. A sample of 299 participants was drawn from academic staff, directors of human resources, and Vice chancellors. Results indicated a weak positive relationship between financial reward and academic staff teaching output in public universities (r=0.282, p<0.01). There existed further a weak positive relationship between financial reward and academic staff research output (r=0.211, p<0.01). It would suffice to effect appropriate financial rewards to academic staff based on a living wage.